SWOT Analysis Marketing Strategy in Increasing the Number of Savings Customers at Bank Financing Rakyat Syariah (BPRS) HIK Parahyangan Ciamis Branch - Nopianti Pebrianta; Nila Nurochani; Ganjar Santika (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research was conducted at BPRS HIK Parahyangan Ciamis, where there are various kinds of products and services that suit customer needs. A good business strategy is needed to face increasingly complex and competitive business competition. The method carried out in this study is qualitative method. Data collection techniques in this study were conducted by interviews and analyzed using SWOT. The data type consists of primary and secondary data. The results of research from the descriptive methodology of SWOT analysis can be obtained matrix values from internal factors of 3.18 and external matrix values of 3.00. From the results of this study, BPRS HIK Parahyangan Ciamis is in quarter I (positive, positive), which shows that the company is in a advantageous position and has strengths and opportunities. And can use these strengths and opportunities to the fullest by implementing strategies that support aggressive growth policies